Numerical 3D Model of Suspended Sediment Transport Downstream Al-Amarah Barrage, Iraq - Ismaeel, Abaas J.; Abbas, Sarmad A.; Al-Rekabi, Wisam S. (Basrah Journal for Engineering Sciences, 2021)
This research is an analytical study for simulation both sediment transport and flow within the Tigris river reach located downstream of the Al-Amarah barrage within the Maysan province. This study adopted a three-dimensional program (SSIIM) which use the Navier-Stokes equations for calculating the flow, and the convection-diffusion equations for calculating the sediment transport by the finite volume method as approximated method. A structured non-orthogonal three-dimensional grid is employed to perform the simulation. The obtained results are subsequently compared to the field measurements. The determination coefficient ( R 2 ) for this comparison is 0.96 for flow velocity distribution and 0.94 for sediment concentration distribution. The results also showed through the simulation of the water flow, the state of the secondary flow and its effect on both the main flow and the erosion of the river bed in the studied cross sections. According to the high convergence of the results of this model with the field measurements, this model is a powerful tool for simulating flow and sediment concentrations in river systems and channels.